Ageing as an Important Risk Factor for Cancer - Smetana, Karel; Lacina, Lukáš; Szabo, Pavol; Dvořánková, Barbora; Brož, Prokop; Šedo, Aleksi (Anticancer research, 2016)
An ageing population is a typical feature of many developed countries across the world. Analyzed from a biomedical and philosophical point of view, this phenomenon is also a potential risk factor for social sustainability of communities. The association between ageing and cancer seems to be more than apparent. Therefore, the further increase of epidemic-like incidence of malignant tumors in a population can be expected in the near future. Elderly people usually suffer from age-dependent diseases, and such polymorbidity can seriously affect the treatment of malignant tumors. Such an impending situation may be associated with multiple medical, social and economic issues. This article summarizes data about the possible molecular mechanism influencing rapid spreading of tumors in the elderly population. Reduction of the activity of DNA repair machinery is a likely genetic cause. Besides this, even epigenetic mechanisms can influence this process. In this context, the role of cancer stroma in controlling multiple biological properties of tumors is a prospective target for translational research with potential therapeutic outcomes.
Keywords: Socioeconomic Factors; Aging; mutace; Neoplasms; Risk Factors; epigeneze genetická; review; DNA repair; cancer microenvironment; socioekonomické faktory; incidence; genetické nemoci vrozené; cancer incidence; Ageing; lidé; Wound Healing; Humans; rizikové faktory; stárnutí; Genetic Diseases, Inborn; genetic instability; nádory; Mutation; Incidence; Epigenesis, Genetic; hojení ran